Epigenetic Function of Activation-Induced Cytidine Deaminase and Its Link to Lymphomagenesis - Dominguez, Pilar M.; Shaknovich, Rita (Frontiers in Immunology, 2014)
Activation-induced cytidine deaminase (AID) is essential for somatic hypermutation (SHM) and class switch recombination (CSR) of immunoglobulin (Ig) genes during B cell maturation and immune response. Expression of AID is tightly regulated due to its mutagenic and recombinogenic potential, which is known to target not only Ig genes, but also non-Ig genes, contributing to lymphomagenesis. In recent years a new epigenetic function of AID and its link to DNA demethylation came to light in several developmental systems. In this review, we summarize existing evidence linking deamination of unmodified and modified cytidine by AID to base-excision repair (BER) and mismatch repair (MMR) machinery resulting in passive or active removal of DNA methylation mark, with the focus on B cell biology. We also discuss potential contribution of AID-dependent DNA hypomethylation to lymphomagenesis.